Pengecekan Tingkat Similaritas Jawaban ChatGPT pada Prompts Pendidikan Kejuruan - Ranu Iskandar; Anik Maghfiroh (Journal of Education and Teaching (JET), 2023)
ChatGPT is one of the AIs that really helps humans in answering all questions in various sectors including in the education sector if used wisely. This research aims to describe the answers of chatGPT related to vocational education using turnitin and chatGPT. This research is a descriptive research. There were 10 questions asked. After 1 answer appears, then click the generate response button to get other answers. Each question was taken 3 answers from ChatGPT. The results of turnitin checking were compared with the plagiarism rate table. The checking was done by pasting the answers plus a question ‘is this answer from chatGPT?’. Based on checking using turnitin, it is known that 8 answers have a low similarity index while 2 answers have a medium similarity index. Based on checking using chatGPT itself, it is known that chatGPT knows all the answers from him. Recommendations for further research are that paraphrase can be done using AI tools such as Wordtune and Quillbot. Then the results are checked for similarity index with many plagiarism tools.